The effect of perceived benefits, ease of use and customer trust on interest reusing mobile banking services - Nugraha, Heri; Hasyim, Muhamad Ardi Nupi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
The Influence of Perceived Benefits, Ease of Use, and Customer Trust on Interest in Reusing Internet Banking/Mobile Banking Services” under the guidance. The purpose of the study is to examine the effect of perceived benefits, ease of use and customer trust on the interest in reusing internet banking/mobile banking services. This study uses quantitative methods (descriptive and associative). Data collection techniques use questionnaires by distributing a list of questions or written statements to be answered or filled out with the number of 100 respondents were taken randomly. Perception of Benefits, Ease of Use and Customer Trust have a significant effect on interest in reusing internet banking/mobile banking services. Based on the respondents, Perceived Benefits and Ease of Use show a strong category, while Customer Trust shows a very strong category. So that the results of the study show: Perception of Benefits, Ease of Use and Customer Trust on the interest in reusing internet banking/mobile banking services at bank OCBC NISP is very strong.